Bueng Selimpat: The Existence of Kutai Tradition Through Philosophical and Spiritual Values - Septiani Eka Syaputri; Asnar Asnar; Alim Salamah; Endang Herliah; Jawatir Pardosi; Wingkolatin Wingkolatin; Suryaningsi Suryaningsi; Reza Reza (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
This study examines the Bueng Selimpat tradition practiced by the Kutai ethnic group in Benua Baru Village as a worldview that links three key elements: humanity, nature, and ancestral heritage. For the Kutai community, rivers serve not only as a resource but are also regarded as the abode of sacred forces believed to be their ancestors. The main objective is to analyze the existence and sustainability of this tradition amid changing times. Using a Husserlian phenomenological approach, data were collected from ten informants: five Kutai residents who still practice, understand, and preserve the tradition, and five university students who offered perspectives on its relevance today. The findings show that Bueng Selimpat has remained preserved and practiced despite cultural acculturation; the community maintains the tradition as ancestral heritage while integrating local cultural values with formal religious teachings. This research enriches studies in the social sciences, provides educational material to instill noble values, fosters harmonious living, and strengthens national unity based on local wisdom that aligns with the values of Pancasila.